Genomewide Association Study of Leisure-Time Exercise Behavior in Japanese Adults - HARA, MEGUMI (Med Sci Sports Exerc, 2018)
PURPOSE: Although several genetic factors may play a role in leisure-time exercise behavior, there is currently no evidence of a significant genomewide association, and candidate gene replication studies have produced inconsistent results. METHODS: We conducted a two-stage genomewide association study and candidate single-nucleotide polymorphisms (SNP) association study on leisure-time exercise behavior using 13,980 discovery samples from the Japan Multi-Institutional Collaborative Cohort (J-MICC) study, and 2036 replication samples from the Hospital-based Epidemiologic Research Program at Aichi Cancer Center-2 study. Leisure-time physical activity was measured using a self-administered questionnaire that inquired about the type, frequency and duration of exercise. Participants with ≥4 MET·h·wk(−1) of leisure-time physical activity were defined as exhibiting leisure-time exercise behavior. Association testing using mixed linear regression models was performed on the discovery and replication samples, after which the results were combined in a meta-analysis. In addition, we tested six candidate genetic variants derived from previous genomewide association study. RESULTS: We found that one novel SNP (rs10252228) located in the intergenic region between NPSR1 and DPY19L1 was significantly associated with leisure-time exercise behavior in discovery samples. This association was also significant in replication samples (combined P value by meta-analysis = 2.2 × 10(−9)). Several SNP linked with rs10252228 were significantly associated with gene expression of DPY19L1 and DP19L2P1 in skeletal muscle, heart, whole blood, and the nervous system. Among the candidate SNP, rs12612420 in DNAPTP6 demonstrated nominal significance in discovery samples but not in replication samples. CONCLUSIONS: We identified a novel genetic variant associated with regular leisure-time exercise behavior. Further functional studies are required to validate the role of these variants in exercise behavior.